Multifunctional Wearable Silver Nanowire Decorated Leather Nanocomposites for Joule Heating, Electromagnetic Interference Shielding and Piezoresistive Sensing - Ma, Zhonglei; Xiang, Xiaolian; Shao, Liang; Zhang, Yali; Gu, Junwei (Angewandte Chemie International Edition, 2022)
Multifunctional wearable electronic devices based on natural materials are highly desirable for versatile applications of energy conversion, electronic skin and artificial intelligence. Herein, multifunctional wearable silver nanowire decorated leather (AgNW/leather) nanocomposites with hierarchical structures for integrated visual Joule heating, electromagnetic interference (EMI) shielding and piezoresistive sensing are fabricated via the facile vacuum‐assisted filtration process. The AgNWs penetrate the micro‐nanoporous structures in the corium side of leather constructing highly‐efficient conductive networks. The resultant flexible and mechanically strong AgNW/leather nanocomposites exhibit extremely low sheet resistance of 0.8 Ω/sq, superior visual Joule heating temperatures up to 108 °C at low supplied voltage of 2.0 V due to efficient energy conversion, excellent EMI shielding effectiveness (EMI SE) of ≈55 dB and outstanding piezoresistive sensing ability in human motion detection. This work demonstrates the fabrication of multifunctional AgNW/leather nanocomposites for next‐generation wearable electronic devices in energy conversion, electronic skin and artificial intelligence, etc. Multifunctional wearable silver nanowire decorated leather (AgNW/leather) nanocomposites with integrated capabilities of Joule heating, electromagnetic interference (EMI) shielding and piezoresistive sensing are fabricated via a facile vacuum‐assisted filtration process. The resultant AgNW/leather nanocomposites show promising application potentials for next‐generation wearable electronic devices in energy conversion, electronic skin and artificial intelligence, etc.